The Influence of Product Quality on Repurchase Decision through Halal Label as a Mediating Variable in Culinary Businesses - Rahayu, Fitri Desiyani; Navilah, Ila; Rokhlinasari, Sri (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2025)
The number of company chicken crushed Which has present in City Cirebon in a number of year final like Bensu's geprek , chicken crushed Mr. Boy , chicken crushed Backpack , chicken crushed Prince and other brands are on the rise diverse make competition in business the more tight , because due to the large number of choice dish chicken crushed with variety of flavors, textures and prices in accordance with quality product Which offered . By Because That , study This aim For analyze How influence quality product chicken crushed Mr. Boy to decision Buy back . Method used in study This is method quantitative and technique taking sample that is purposive sampling applied to the sample selected that produces 100 respond legitimate. Analysis data technical Which used is track analysis. Research result show that variables quality product own mark statistics T as big as 4,940 prob 0.000 ≤ 0.05 which means that quality product influential significant regarding halal labels, quality products also affect decision buy back , matter This proven with The t-stat value is 6.391, prob 0.000 ≤ 0.05, the halal label variable influences decision buy back , thing This proven with mark t statistic of 2.502 and p value of 0.015 ≤ 0.05, and the variable quality product No influential to decision buy back through halal label, thing This proven with Sobel test value of 0.223 ≤ t table 1.984.